PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PERUM BULOG DIVISI REGIONAL JAWA BARAT - Luthfia Nur Wachidah; Bachruddin Saleh Luturlean (Jurnal Ilmiah MEA (Manajemen, Ekonomi, & Akuntansi), 2019)
The purpose of this research was to determine the effect of work discipline on employee performance at Perum BULOG Divisi Regional Jawa Barat. This type of research is descriptive causal with quantitative methods. Data analysis used with descriptive analysis and simple linear regression analysis. This study uses saturated samples as many as 69 employees of Perum BULOG Divisi Regional Jawa Barat as respondents. The results of this study indicate that work discipline has a positive and significant effect on the performance of Perum BULOG Divisi Regional Jawa Barat employees, with t-count of 8.730 greater than t-table 1.998 and significance 0.000. Work discipline variables affect performance with a contribution of 53.2%. Based on the results of the study, it was concluded that work discipline had a significant effect on the performance of Perum BULOG Divisi Regional Jawa Barat employees with a contribution of 53.2%. Based on the results of the study, it was concluded that work discipline had an effect on employee performance by 53.2% on the performance of Perum BULOG Divisi Regional Jawa Barat employees, while the remaining 46.8% was influenced by other variables not examined in this study.